PENGOLAHAN LIMBAH INDUSTRI BENANG MENGGUNAKAN KOMBINASI FILTRASI MEDIA BIOCHAR DAN CONSTRUCTED WETLANDS - Novirina Hendrasarie; Nurma Syitoh (EnviroUS, 2022)
Processing wastewater filtration systems and Constructed Wetlands systems have been widely used with the use of natural materials to reduce waste content and have aesthetic value which is the main attraction of this research. This study aims to determine the effectiveness of the filter media in the form of biochar husk and anthracite and the types of plants (Zantedeschia aethiopica and Epipremnum aureum) used in the Constructed Wetlands. The main parameters used are COD, TSS, Ammonia, and color. Reactor wetlands have residence times ranging from 3 days, 6 days, 9 days, 12 days to 15 days. The residence time of the waste filtration process is 5 hours. The best filtration using anthracite filter media has an efficiency of removal of COD, TSS, Ammonia, Color of 40.86%, respectively; 31.71%; 15.8%; 9.78%. The best Constructed Wetlands system is in a reactor containing an Epipremnum aureum inlet plant from anthracite filtration effluent which has an efficiency of removing COD, TSS, Ammonia, and color parameters of 77.4%; 86.43%; 91.38%; 97.7%.